A cabinet secretary looks back - Deshmukh, B. G. (Bhalchandra Gopal), 1929- (New Delhi ; New York, N.Y. : HarperCollins Publishers India a joint venture with India Today Group, 2004)
Service memoirs of Bhalchandra Gopal Deshmukh, b. 1929, a former Indian cabinet secretary; includes autobiographical references.
Includes index.
Keywords: Deshmukh, B. G. -- 1929-; Government executives -- India -- Biography; Civil service -- India -- Biography